On the nature of cross-linguistic transfer: A case study of Andean Spanish - MUNTENDAM, ANTJE G. (Bilingualism (Cambridge, England), 2013)
This paper presents the results of a study on cross-linguistic transfer in Andean Spanish word order. In Andean Spanish the object appears in preverbal position more frequently than in non-Andean Spanish, which has been attributed to an influence from Quechua (a Subject–Object–Verb language). The high frequency of preverbal objects could be explained by focus fronting. The main syntactic properties of focus fronting in Spanish are weak crossover and long distance movement. Two elicitation studies designed to test for these properties in non-Andean Spanish, Andean Spanish and Quechua show no evidence of syntactic transfer from Quechua into Andean Spanish. Rather, the analysis of naturalistic data and an elicitation study on question–answer pairs show that there is pragmatic transfer from Quechua into Andean Spanish. The study has implications for theories of syntax and language contact, and especially for the debate on the nature of cross-linguistic transfer.